Determinants Of Corporate Sustainability Performance: The Effects Of Corporate Strategy And Institutional Quality In Asean Region - Ab Wahab, Siti Nur Aqilah (2024)
In addition to ASEAN’s national development plans, ASEAN countries have developed and evaluated plans for sustainability development goals (SDGs). Nonetheless, with only eight years remaining until the SDGs vision of 2030, implementing sustainable development activities in ASEAN countries is far behind what the United Nations had originally envisioned. Compared to other developed nations, the corporate sustainability performance (CSP) in ASEAN countries is currently poor. This study aims to investigate the factors that influence corporate sustainability performance in ASEAN countries. This study examined three important variables: corporate governance, environmental degradation and financial development that influenced CSP. Furthermore, the study investigates how corporate strategy and institutional quality have a threshold effect on CSP. Using the Static Panel and Panel Threshold effect estimator, this study utilised 118 firms listed on the ASEAN stock exchange between 2011 and 2020. The study validates the female directors and of independent directors on ASEAN boards positively impacts corporate sustainability. Intriguingly, the intervention of corporate strategy will mitigate the low corporate sustainability performance while strengthening the link between corporate governance and CSP. During the sample period, ASEAN firms are positively influenced by external factors that affect CSP (financial development and environmental degradation).